FAKTOR ORGANISASI YANG MEMPENGARUHI KINERJA (STUDI PADA PERAWAT IGD RSUD ULIN BANJARMASIN) - Rina Annisa (Islamic University of Kalimantan MAB Banjarmasin, 2017)
Emergency Installation (EI) is the first place for patients to get emergency treatment. Successful EIs are not solely about the availability of support facilities, but also human resource performance measured from organizational factors, such as nursing management, leadership style, incentives, organizational structure and job design are included. The main purpose of this study is to partially and simultaneously test the influence of organizational factors on nurse performance with descriptive method with quantitative analytic approach. The sampling technique used a census approach of 33 nurses at the Emergency Installation, Banjarmasin Ulin Hospital. All data were obtained by distributing questionnaires and analyzed by using multiple regressions. The result of data analysis shows that nursing management, transformational style, and work design have positive but not significant influence on nurse's performance. Incentives and organizational structures have a positive and significant influence on nurse performance. Organizational factors simultaneously positive effect on the performance of nurses in the Emergency Installation Banjarmasin Ulin General Hospital for 55.10% and the remaining 44.90% influenced by other variables.Keywords: Organization Factor, Nurse Performance, Emergency Installation.